Use of microseisms in storm diagnosis (MAUSAM, 1983)
Microseisms generated by storms in the Bay of Bengal and recorded by Sprengnether micro-seismographs at Visakhapatnam and Madras and by Milne-Shaw seismograph at Port Blair have been studied. The amplitude of microseisms had a primary maximum when the storm is at peak intensity and a secondary maximum when the storm crosses the coast. Microseisms amplitudes AM, AV and AP respectively recorded at Madras, Visakhapatnam and Port Blair during 1961 to 1970 were taken. The ratios AM/ AV and AP/ AM were plotted on two separate maps at the corresponding storm position as given in IDWR and thus two sets of amplitude ratio isolines were obtained. The clear-cut inter-sections of these two sets of isolines enabled us to locate the storm position when amplitude ratios are known. We applied these amplitude ratio charts for locating storm during 1971 and 1972. The location by this method was found to agree within 0.5 deg. in latitude or longitude as compared to the determination given in Indian Daily Weather Report (IDWR). Amplitude recorded at Madras when the storm was at severe cyclonic stage were plotted at storm centre and isolines (amplitude charts) were drawn through these amplitude values. It seems that preparation of such a chart for determining storm intensity requires more precise specification of storm ( such as maximum wind speed ).